Brain tumor research in the United Kingdom: current perspective and future challenges. A strategy document from the NCRI Brain Tumor CSG. Issue 1 (30th August 2017) - Kurian, Kathreena M; Jenkinson, Michael D; Brennan, Paul M; Grant, Robin; Jefferies, Sarah; Rooney, Alasdair G; Bulbeck, Helen; Erridge, Sara C; Mills, Samantha; McBain, Catherine; McCabe, Martin G; Price, Stephen J; et al.
Abstract: The National Cancer Research Institute (NCRI) is a partnership of charity and government research funders whose purpose is to improve health and quality of life by accelerating progress in cancer-related research through collaboration. Under this umbrella, the NCRI Brain Tumor Clinical Studies Group is focused on improving clinical outcomes for adult patients with brain and central nervous system tumors, including those with brain metastasis from other primary sites. This document discusses the current state of clinical brain tumor research in the United Kingdom and the challenges to increasing study and trial opportunities for patients. The clinical research priorities are defined along with a strategy to strengthen the existing brain tumor research network, improve access to tissue and imaging and to develop the future leadership for brain tumor research in the United Kingdom. This strategy document may serve as a framework for other organizations and countries.